EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) DAN THINK PAIR SHARE (TPS) DENGAN PENDEKATAN SAINTIFIK PADA MATERI HIMPUNAN DITINJAU DARI AKTIVITAS BELAJAR - Agung Nugroho, Tri Wahyu; Mardiyana, Mardiyana; Sari Saputro, Dewi Retno (Jurnal Pembelajaran Matematika, 2016)
Abstract: The aim of the research was to know the effect of learning models on mathematics learning achievement viewed from the students learning activity. The learning models compared were the cooperative learning model of the numbered heads together with scientific approach (NHT-S), the cooperative learning model of the Think Pair Share with scientific approach (TPS-S), and model of classical learning with scientific approach (K-S). The type of the research was a quasi experimental research with the factorial design of 3 x 3. The population were all seventh grade students of Junior High School in Temanggung regency on academic year 2014/2015. The samples of the research were taken by using the stratified cluster random sampling. The instruments used were mathematics achievement test and learning activities questionnaires. The hypotheses of the research was analyzed by using the two-way analysis of variance with unbalanced cells at the significance level of . The results of the research were as follows. 1) NHT-S gave better mathematics achievements than TPS-S and K-S. Both TPS-S and K-S gave the same mathematics achievements. 2) Students with high learning activity gave better mathematics achievements than students with medium learning activity and low learning activity, while students with medium learning activity got mathematics achievements as good as students with low learning activity. 3) For NHT-S, students with high learning activity and medium learning activity got the same mathematics achievements, students with high learning activity got better mathematics achievements than student with low learning activity, and students with medium learning activity and low learning activity got same mathematics achievements. For TPS-S and K-S, student with high, medium, and low learning activity got the same mathematics achievements. 4) For students with high and medium learning activity, NHT-S gave better mathematics achievements than TPS-S , both NHT-S and TPS gave the same mathematics achievement with K-S. For students with low learning activity , NHT-S, TPS-S and K-S gave the same mathematics achievements.Keywords: NHT, TPS, Classical, Scientific Approach, Learning Activity